Learning Transferable Lessons from Single Cases in Comparative Policy Analysis. Issue 4 (8th August 2018) - Wolf, Amanda; Baehler, Karen J.
ABSTRACT: Policy exemplars offer potential value to policy professionals seeking new ideas. Realizing that value typically assumes a learner who is both equipped with a well-specified policy or process objective and able to model causal connections to extract lessons. Yet there is a gap in explicating how, exactly, policy professionals find ideas worth pursuing. This article draws on the concepts of abduction and phronesis – broadly a flash of insight and practical judgement, occasioned by an observation – to fill that gap. The natural capabilities associated with abduction and phronesis rely on noticing what stands out, making analogical connections, and discerning which connections merit following up. With attention to these capabilities, policy professionals can extend their learning of transferable lessons from single cases.